THE IMPACT OF SHADOW EMPLOYMENT ON THE ECONOMY OF UKRAINE: ANALYSIS AND REASONS - Demkovych, Tetiana (Socio-economic relations in the digital society, 2023)
This article examines the impact of shadow employment on the economic sector in Ukraine and investigates the reasons for its emergence using statistical, systemic, and functional methods of scientific research. The research aims to summarize the theoretical aspects of shadow employment, analyze the current state of shadow employment in Ukraine and its impact on the economy, as well as systematize possible ways to reduce it. The legalization of labour relations is a highly relevant and pressing issue today, as the prevalence of shadow employment is evident, including tax evasion, illegal employment, and reduced financial contributions to the state budget. This is why this article focuses on analyzing the dynamics of shadow employment in Ukraine across various economic sectors and its overall impact on the employed population, based on the data from the State Statistics Service of Ukraine. It also analysis the report on the «Impact of the COVID-19 pandemic on the legal needs of informally employed individuals in Ukraine» by the Network of Legal Development, particularly the data related to the sectors in which formally and informally employed people work, the reasons for informal employment among the informally employed, incentives for informal employment among the formally employed, and factors that will promote formal employment from the perspectives of both formal and informal workers, etc. Furthermore, a scheme outlining strategies to reduce the influence of shadow employment on Ukraine’s economy is developed. It shows that to minimize shadow employment effective changes are needed not only in the quality of public services and governance system but also in providing improved working conditions, and social benefits to enhance productivity and labour efficiency.